2009
DOI: 10.1159/000210378
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Ginsan on the Development of Allergic Reaction in Murine Asthmatic Model

Abstract: Background: Asthma is a major health problem worldwide, and the morbidity and mortality caused by asthma are on the rise. Corticosteroid therapies for asthma treatment frequently induce many side effects. Therefore, the development of new medicines that have both high efficacy and fewer side effects has been a scientific challenge. Here we tested the effect of ginsan, a polysaccharide derived from Panax ginseng, against allergic reaction in an ovalbumin (OVA)-induced murine asthmatic model in comparison with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 71 publications
(53 reference statements)
1
23
0
Order By: Relevance
“…We have found that Ginsan, which have been popularly used in the oriental medicine, could provide protection against bacterial infection by modulating COX-1 expression. In our previous work with a murine asthma model, the suppressive effect of Ginsan was also mediated by modulating COX expression in the lung (13) which is consistent with our current finding. Further studies are required to determine the protein expression and its products including prostaglandins.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We have found that Ginsan, which have been popularly used in the oriental medicine, could provide protection against bacterial infection by modulating COX-1 expression. In our previous work with a murine asthma model, the suppressive effect of Ginsan was also mediated by modulating COX expression in the lung (13) which is consistent with our current finding. Further studies are required to determine the protein expression and its products including prostaglandins.…”
Section: Discussionsupporting
confidence: 92%
“…Also, Ginsan possesses a potent anti-septicemic activity (6,16). Furthermore, Ginsan can suppress the development of allergic reaction in an asthmatic model by modulating mucosal immune responses (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma treatment by corticosteroid frequently induced many side effects. For the purpose of finding a safe and high efficacy substitute, Lim et al (2009) evaluated the effect of ginsan against allergic reaction in an ovalbumin (OVA)-induced murine asthmatic model in comparison with dexamethasone, and investigated its underlying mechanism. To elucidate the mechanism of ginsan, expression of inflammation-related genes were screened.…”
Section: Antiasthmatic Activity Antidepressant Activity Qi-invigoramentioning
confidence: 99%
“…Red Ginseng root extracts have also been used for the treatment of atopic suppurative dermatitis, wounds, inflammation of the skin, and allergic diarrhea. There are reports that ginseng saponins and/or extracts have anti-allergic properties including effects on asthma and dermatitis Park et al, 2003Park et al, , 2004Shi et al, 2005;Bae et al, 2006;Shin et al, 2006a,b;Kim et al, 2008a,b;Bayayigit et al, 2008;Lim et al, 2009). Food allergies are common allergic diseases with a substantial risk of life-threatening anaphylactic reactions.…”
Section: Introductionmentioning
confidence: 99%